IL-33 stimulates the release of procoagulant microvesicles from human monocytes and differentially increases tissue factor in human monocyte subsets - Stojkovic, Stefan; Thulin, Åsa; Hell, Lena; Thaler, Barbara; Rauscher, Sabine; Baumgartner, Johanna; Gröger, Marion; Ay, Cihan; Demyanets, Svitlana; Neumayer, Christoph; Huk, Ihor; Spittler, Andreas; Huber, Kurt; Wojta, Johann; Siegbahn, Agneta; Åberg, Mikael (Thrombosis and Haemostasis, 2017)
Monocytes and monocyte-derived microvesicles (MVs) are the main source of circulating tissue factor (TF). Increased monocyte TF expression and increased circulating levels of procoagulant MVs contribute to the formation of a prothrombotic state in patients with cardiovascular disease. Interleukin (IL)-33 is a pro-inflammatory cytokine involved in atherosclerosis and other inflammatory diseases, but its role in regulating thrombosis is still unclear. The aim of the present study was to investigate the effects of IL-33 on the procoagulant properties of human monocytes and monocyte-derived MVs. IL-33 induced a time- and concentration-dependent increase of monocyte TF mRNA and protein levels via binding to the ST2-receptor and activation of the NFκB-pathway. The IL-33 treated monocytes also released CD14+TF+ MVs and IL-33 was found to increase the TF activity of both the isolated monocytes and monocyte-derived MVs. The monocytes were classified into subsets according to their CD14 and CD16 expression. Intermediate monocytes (IM) showed the highest ST2 receptor expression, followed by non-classical monocytes (NCM), and classical monocytes (CM). IL-33 induced a significant increase of TF only in the IM (p<0.01), with a tendency in NCM (p=0.06), but no increase was observed in CM. Finally, plasma levels of IL–33 were positively correlated with CD14+TF+ MVs in patients undergoing carotid endarterectomy (r=0.480; p=0.032; n=20). We hereby provide novel evidence that the proinflammatory cytokine IL-33 induces differential TF expression and activity in monocyte subsets, as well as the release of procoagulant MVs. In this manner, IL-33 may contribute to the formation of a prothrombotic state characteristic for cardiovascular disease.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Interleukin-33; tissue factor; monocyte subsets; microvesicles; thrombosis